2020
DOI: 10.3390/brainsci10050275
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Alcohol Drinking in Non-Dependent and Dependent Mice Following Repeated Cycles of Forced Swim Stress Exposure

Abstract: Chronic stress is a known contributing factor to the development of drug and alcohol addiction. Animal models have previously shown that repeated forced swim stress promotes escalated alcohol consumption in dependent animals. To investigate the underlying molecular adaptations associated with stress and chronic alcohol exposure, RNA-sequencing and bioinformatics analyses were conducted on the prefrontal cortex (CTX) of male C57BL/6J mice that were behaviorally tested for either non-dependent alcohol consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Acute alcohol exposure induces Hspa1a in human monocytes and is required for inhibition of TLR4/MyD88 (but not TLR4/TRIF) signaling in macrophages [ 63 ]. Hspa1a and Hspa1b transcripts are also dysregulated after ethanol exposure in rodent in total brain homogenates [ 64 66 ], astrocytes [ 67 , 68 ], and microglia [ 68 ]. Depending on the time point at which gene expression was assayed and perhaps other differences between the protocols employed, these studies have shown increases or decreases in their transcript abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Acute alcohol exposure induces Hspa1a in human monocytes and is required for inhibition of TLR4/MyD88 (but not TLR4/TRIF) signaling in macrophages [ 63 ]. Hspa1a and Hspa1b transcripts are also dysregulated after ethanol exposure in rodent in total brain homogenates [ 64 66 ], astrocytes [ 67 , 68 ], and microglia [ 68 ]. Depending on the time point at which gene expression was assayed and perhaps other differences between the protocols employed, these studies have shown increases or decreases in their transcript abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work with the same animals identified transcriptional changes associated with CIE+FSS in the mouse cortex[22]. Cortical transcriptional signatures from the same alcohol-dependent, stressed animals provide an opportunity to identify overlapping gene expression changes between PFC and NTS.…”
Section: Resultsmentioning
confidence: 98%
“…The present data demonstrate that apremilast effectively reduces ethanol intake in stressed and non-stressed alcohol dependent and non-dependent mice. Notably, others have found that male C57BL/6J mice subjected to forced swim stress and CIE had persistent increases in immune-related, alcohol responsive genes, including Pde4b expression 57 . Moreover, previous work showed that nonspecifically targeting phosphodiesterases (via peripheral administration of ibudilast) reduced dependence-induced alcohol intake in C57BL/6J mice 49 .…”
Section: Discussionmentioning
confidence: 99%